A Multicenter, Open-Label Trial to Evaluate the Quality of Life in Adults With ADHD Treated With Long-Acting Methylphenidate (OROS MPH): Concerta Quality of Life (CONQoL) Study. (July 2013) - Mattos, Paulo; Louzã, Mário Rodrigues; Palmini, André Luís Fernandes; Oliveira, Irismar Reis de; Rocha, Fábio Lopes
The available literature provides few studies on the effectiveness of methylphenidate in improving quality of life in individuals with ADHD.Objective: To assess the effectiveness of Methyphenidate OROS formulation (OROS MPH) through QoL in adults with ADHD.Method: A 12-week, multicenter, open-label trial involving 60 patients was used. The measures used were Adult Self-Rating Scale, Adult ADHD Quality of Life Scale (AAQoL), State and Trait Anxiety Inventory (STAI), Hamilton Depression Rating Scale (HAM-D), Clinical Global Impression (CGI), and safety measures. A significance statistic level of 5% was adopted.Results: Analyses included 60 patients (66.7% male; M age = 31.1 years) for safety and 58 patients for effectiveness. All AAQoL subscales improved from baseline to Week 12 ( p < .0001), as well as the Total AAQoL ( p < .0001). A significant reduction on Clinical Global Impression–Improvement (CGI-I), HAM-D, STAI, and ASRS scores was observed ( p < .0001). No serious adverse event was reported.Conclusion: Treatment of adult ADHD patients with OROS MPH improves QoL.